Renegotiation-Proof Third-Party Contracts under Asymmetric Information - Emanuele Gerratana; Levent Koçkesen (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
This paper characterizes the equilibrium outcomes of two-stage games in which the second mover has private information and can sign renegotiable contracts with a neutral third-party. Our aim is to understand whether renegotiation-proof third-party contracts can confer a strategic advantage on the second mover. We first analyze non-renegotiable contracts and show that a "folk theorem" holds: Any outcome in which the second mover best responds to the first mover's action and the first mover obtains a payoff at least as large as his "individually rational payoff" can be supported. Renegotiation-proofness imposes some restrictions, which is most transparent in games with externalities, i.e., games in which the first mover's payoff increases (or decreases) in the second mover's action. In such games, a similar folk theorem holds with renegotation-proof contracts as well, but the firstmover's individually rational payoff is in general higher.
Keywords: C72; D80; L13; 330; Third-Party Contracts; Strategic Delegation; Renegotiation; Asymmetric Information; Renegotiation-Proofness; Durability; Gleichgewichtsmodell; Nichtkooperatives Spiel; Asymmetrische Information; Unvollkommener Markt; Entscheidungstheorie